دقلديانوس ودوره في الامبراطورية الرومانية (284 – 305م) - خيرة خلدون; د/ احمد حمدي (جامعة عمار ثليجي الاغواط, 2023)
الملخص شهد العالم القديم ظهور العديد من الحضارات في مختلف ارجاءه، ومن بين تلك الحضارات الحضارة الرومانية، في أواخر القرن الأول قبل الميلاد بدا العصر الامبراطوري على يد أغسطس، وفي أواخر الاسرة السيفيرية َبدات فترة اضطرابات وصراعات عسكرية وتردت الأوضاع حتى كادت تنهار الإمبراطورية لولا ان تولى الحكم في أواخر القرن الثالث ميلادي الامبراطور دقلديانوس، والذي بدا معه عهد جديد لما قام به من اصلاحات من اجل انقاذ الإمبراطورية، قرر دقلديانوس احداث التيترارشية ، والقيام ببعض التعديلات والإصلاحات السياسية، الإدارية، والعسكرية، وشن حملة اضطهاد المسيحيين، ولعل اهم اصلاحاته هي تلك المتعلقة بالمالية والضرائب. - والاشكالية تتمحورحول : "ما هو دور دقلديانوس في الإمبراطورية الرومانية؟". الكلمات المفتاحية : العصر الامبراطوري - القرن الثالث ميلادي – الامبراطور دقلديانوس -اصلاحات. Abstract The ancient world witnessed the emergence of many civilizations in various parts, among those civilizations is the Rome cinilizataion, of in the late first century BC, the the imperial era begans at the hands of August, in the late Savior family, a period of meilitary unrest and and conflicts began to be not been for the rule in the late third center AD Epperror Diocletian, and with whom he appeared a new era for his efforts to save the empire, Diocletian decided the events of the Tetrichi, and carried out political, administrative and military reforms, the measures to persecute of the empire. -And the problem revolves arond : ‘’ What is Diocletian’s role in the Roman Empire ?’’. Keywords : The imperial ara,Third century AD, Emperor Diocletian, Repairs.